EXTENDED-RELEASE METHYLPHENIDATE DELIVERY SYSTEMS IN ATTENTION-DEFICIT/HYPERACTIVITY DISORDER: PHARMACOKINETIC PROFILES AND CLINICAL IMPLICATIONS FOR INDIVIDUALIZED TREATMENT - Miranda Neto, José Jorge de; Macedo, Maria Luisa Miranda (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is a highly prevalent neurodevelopmental condition with onset in childhood and functional impairment that may persist into adulthood. Methylphenidate remains a first-line pharmacological treatment due to its well-established efficacy and safety profile (Wolraich et al., 2019). However, clinically relevant variability in treatment response is frequently observed, partly related to differences in pharmacokinetic characteristics among available formulations. Extended-release (ER) methylphenidate formulations were developed to improve adherence and provide sustained symptom control throughout the day. Importantly, ER formulations are not pharmacokinetically equivalent, as distinct drug delivery technologies result in different absorption patterns, peak plasma concentrations, and duration of effect (Swanson et al., 2003; Childress et al., 2019). This narrative review synthesizes current evidence on the neurobiological basis of ADHD and examines the pharmacology and pharmacokinetic profiles of ER methylphenidate formulations, with particular emphasis on osmotic-controlled release oral delivery system (OROS®) and spheroidal oral drug absorption system (SODAS®) technologies, highlighting implications for individualized treatment strategies.